5G wireless communication system in healthcare informatics - Gupta, M. (Manoj); Kumar, Arun (Associate professor of electronics); Agarwal, Basant; Cengiz, Korhan; Singh, Ghanshyam (Electronics engineer) (CRC Press, 2023)
"This reference text focusses on estimating the performance, cost, and accommodation of the next generation technologies design for IoT, and modern health-care. It will be an ideal reference text for graduate students, academic researchers, and professionals in the fields of electrical, and electronics and communication engineering"--